Joke or threat? Competing genre uptakes in a Danish court case - Bojsen-Møller, Marie (Language and Law / Linguagem e Direito, 2024)
This article examines a Danish criminal case concerning a high school student who posted a picture on Instagram with the caption ‘I’ll be the next school shooter guys, lmao, watch out’ (Danish: jeg bliver den næste school shooter guys, lmao, watch out). Reactions to – or uptakes on (Freadman, 1994) – the Instagram post were split between two distinct types; some took it as a threat and some took it as a joke. Building on theory on threatening communications (e.g. Fraser, 1998; Solan & Tiersma, 2005; Gales, 2019, author et al., 2020), theory on humor (Billig, 2005; Norrick, 2010; Tsakona, 2017) and genre theory (Miller, 1984; Devitt, 2009; Freadman, 2012, 2020), this article studies these diverging uptakes as they are presented within the court case through both transcripts of audio recordings from the court room and court documents.The findings of this study show that while linguistic interpretation is mostly limited to the netcronym ‘lmao’, different non-linguistic behavior is often used as justification for the diverging interpretations of the linguistic behavior. Not only the utterance itself, but also the context of the utterance, including its uptakes, have a bearing on the outcome of the case and the assessment of the defendant’s intent. As such, this study offers important insight into an area that Gales (2019) argues is in need of further interdisciplinary research, namely how contextual features can influence the outcome of criminal cases concerning disputed threats.